A Contribution to Guide the Use of Support Tools for Technology Roadmapping: a Case Study in the Clothing industry - Ibarra G,Cindy J. (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2013)
This article presents guidelines regarding the use of tools to support technology roadmapping based on a case study of an exploratory and descriptive nature in a small company in the clothing sector. After introducing a systematic approach to technology roadmapping with their support tools, an empirical analysis is then presented of the application of the tools of the market layer - a questionnaire for consultation with the consumers and bibliographical research - and the business layer - SWOT matrix, through illustrative examples. Each tool was analyzed in relation to the complexity, time, cost of implementation, relevance and quality of the resulting information, the most common problems associated with their use. Here we show that the tools of the market layer proved to be easiest to use when compared with the tools of business layer, varying the time required, but involving, in general, a low cost in its application to obtain relevant and quality results for the development of the roadmap. Based on the results, general guidelines for the use of these tools to assist in the process of technology roadmapping were established as well as a comparison between the tools.